Assessment of Geodetic Mission Satellite Altimeter Sea Surface Height Data for Developing Marine Gravity Anomaly Models - Akbar Wahyu Nugraha; Dudy Darmawan Wijaya (LPPM Politeknik Aceh Selatan, 2024)
Marine gravity anomalies are critical for various applications, including the analysis of oceanic faults, bathymetry prediction, and the development of marine geoids. These anomalies can be measured using shipborne and airborne gravimetry, both of which offer high accuracy and resolution but are limited by their spatial coverage. Conversely, satellite altimetry provides comprehensive global coverage, making it a valuable tool for studying marine gravity anomalies on a larger scale. This research investigates the effectiveness of satellite altimetry in generating marine gravity anomaly data for the eastern Indonesian seas (6°N-6°S and 115°E-135°E). The study employs spectral analysis of Sea Surface Height (SSH) data to identify dominant components and their spatial resolution. Subsequently, the SSH data is used to calculate marine gravity anomalies via the Inverse Vening Meinesz (IVM) method. The accuracy of these satellite-derived anomalies is validated against shipborne gravimetry measurements. Results indicate that satellite altimetry can produce marine gravity anomalies with an accuracy ranging from 4.130 to 9.547 mGal and a spatial resolution of 11.75 kilometers.